RISKY INVESTMENT DECISIONS OF THE ELDERLY - Kaldarov, Sanzhar (Nazarbayev University School of Sciences and Humanities, 2021)
This paper analyzes the risky investment decisions of the elderly in the United States. Utilizing the Health and Retirement Study data for 2002-2008, I first exam ine the effects of different factors on risky asset ownership employing the Heckman’s two-step model. I then investigate the existence of a causal relationship between health and wealth using the instrumental variable method. I discover that the in centives generated by the U.S. pension system are of paramount importance for the risky asset investment behavior of the elderly. Those covered by private pension plans, in particular a defined contribution plan, are found to be more prone to risk taking. The effect of retirement on risky asset ownership varies by wealth with the wealthy elderly investing more in risky assets when they retire. The bequest motive, measured by number of kids, is found to decrease the investment in risky assets at the intensive margin for both singles and couples. Yet the elderly couples having kids are found to be more likely to invest in risky assets at the extensive margin. I additionally find that wealth has a sizeable positive effect on the health of the elderly.
Keywords: Type of access: Open Access; risky investment decisions; United States